2008
DOI: 10.1039/b805024d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium and osmium carbonyl clusters incorporating stannylene and stannyl ligands

Abstract: SummaryThe reaction of [Ru 3 (CO) Cluster 3 has a superficially similar planar metal core, but with a different bonding mode with respect to that of 1. The Ph 2 Sn group is bonded most closely to Os(2) and Os (3) [2.7862 (3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…These bond parameters suggest that three SiPh 2 ligands are bonded to the central palladium atom giving rise to Si centers with distorted trigonal‐bipyramidal geometries 17. A similar μ 3 ‐coordination mode has recently been reported for germylene (GeR 2 ) and stannylene (SnR 2 ) ligands to three Ru atoms [Ru 3 (CO) 8 (μ‐SPh) 2 (μ 3 ‐EPh 2 )(EPh 3 ) 2 ] (E=Ge, Sn) 18. The {Pd 4 Si 3 } core is stabilized by bonds between Pd out and Si atoms that are weaker than Pd cent Si bonds, in addition to a d 10 –d 10 interaction between the Pd cent and Pd out atoms 19.…”
supporting
confidence: 71%
“…These bond parameters suggest that three SiPh 2 ligands are bonded to the central palladium atom giving rise to Si centers with distorted trigonal‐bipyramidal geometries 17. A similar μ 3 ‐coordination mode has recently been reported for germylene (GeR 2 ) and stannylene (SnR 2 ) ligands to three Ru atoms [Ru 3 (CO) 8 (μ‐SPh) 2 (μ 3 ‐EPh 2 )(EPh 3 ) 2 ] (E=Ge, Sn) 18. The {Pd 4 Si 3 } core is stabilized by bonds between Pd out and Si atoms that are weaker than Pd cent Si bonds, in addition to a d 10 –d 10 interaction between the Pd cent and Pd out atoms 19.…”
supporting
confidence: 71%
“…More recently other tin-element oxidative-addition reactions have been exploited, for example Gárate-Morales and Fernández-G have prepared amine-containing osmium-tin compounds via the cleavage of the nitrogen-tin bond in aminostannanes [27][28][29]. Our group have shown that tetraphenylthiostannane is an excellent source for the inclusion of both tin and sulfur atoms into transition metal clusters [30], reaction of Ru 3 (CO) 12 with Ph 3 Sn-SPh affording bimetallic [Ru 3 (CO) 8 (SnPh 3 ) 2 (µ 3 -SnPh 2 )(µ-SPh) 2 ] resulting from both tin-sulfur and tin-carbon bond cleavage (Scheme 1) [30,31]. 3 (CO) 2…”
Section: Introductionmentioning
confidence: 99%
“…[17] A similar m 3coordination mode has recently been reported for germylene (GeR 2 ) and stannylene (SnR 2 ) ligands to three Ru atoms [Ru 3 (CO) 8 (m-SPh) 2 (m 3 -EPh 2 )(EPh 3 ) 2 ] (E= Ge, Sn). [18] The {Pd 4 Si 3 } core is stabilized by bonds between Pd out and Si atoms that are weaker than Pd cent À Si bonds, in addition to a d 10 -d 10 interaction between the Pd cent and Pd out atoms. [19] The 31 P{ 1 H} NMR spectrum of 2 displayed a single signal (d = À2.41 ppm) flanked by satellite signals of 29 Si nuclei (J-(P,Si) = 22 Hz).…”
mentioning
confidence: 99%